Extracellular vesicles as modifiers of antibody‐drug conjugate efficacy. Issue 4 (13th February 2021) - Barok, Mark; Puhka, Maija; Yazdi, Narjes; Joensuu, Heikki
Abstract: Antibody‐drug conjugates (ADCs) are a new class of anti‐cancer drugs that consist of a monoclonal antibody, a highly potent small‐molecule cytotoxic drug, and a chemical linker between the two. ADCs can selectively deliver cytotoxic drugs to cancer cells leading to a reduced systemic exposure and a wider therapeutic window. To date, nine ADCs have received marketing approval, and over 100 are being investigated in nearly 600 clinical trials. The target antigens of at least eight out of the nine approved anti‐cancer ADCs and of 69 investigational ADCs are present on extracellular vesicles (EVs) (tiny particles produced by almost all types of cells) that may carry their contents into local and distant cells. Therefore, the EVs have a potential to mediate both the anti‐cancer effects and the adverse effects of ADCs. In this overview, we discuss the mechanisms of action of ADCs and the resistance mechanisms to them, the EV‐mediated resistance mechanisms to small molecule anti‐cancer drugs and anti‐cancer monoclonal antibodies, and the EVs as modifiers of ADC efficacy and safety.